Common Fixed Point Results for Generalized g−αsp, ψ, φ Contractive Mappings with Applications. (16th June 2021) - Li, Jianju; Guan, Hongyan
Abstract : In this paper, we introduce a new class of g − α s p − admissible mappings and prove some common fixed point theorems involving this new class of mappings which satisfy generalized contractive conditions in the framework of b − metric spaces. We also provide two examples to show the applicability and validity of our results. Meanwhile, we present an application to the existence of solutions to an integral equation by means of one of our results.